Comparing the Health Workforce Provider Mix and the Distance Travelled for Mental Health Services by Rural and Urban Medicare Beneficiaries. Issue 4 (18th August 2020) - Andrilla, C. Holly A.; Garberson, Lisa A.; Patterson, Davis G.; Quigley, Tim F.; Larson, Eric H.
Abstract: Purpose: To describe the mix of health professionals who care for rural and urban seniors suffering from mood and/or anxiety disorders, the quantity of services they receive, and to understand where beneficiaries receive care for mood and/or anxiety disorders and the distance and time they travel for care. Methods: We used 2014 Medicare administrative claims data to examine access to health care for fee‐for‐service Medicare beneficiaries aged ≥ 65 years who received outpatient services for mood and anxiety disorders. We classified providers into 9 categories: (1) family physicians/general practice, (2) internists, (3) nurse practitioners (NPs) and physician assistants (PAs), (4) psychiatrists, (5) psychologists, (6) clinical social workers, (7) emergency medicine physicians, (8) other physicians, and (9) other providers. We calculated the 1‐way driving distance and travel time between the beneficiary residence and provider location. We classified beneficiaries into 1 of 4 geographic categories based on their residence ZIP Code. Findings: Urban beneficiaries had an average of 2.7 visits for mood and anxiety disorders, while rural beneficiaries had 2.4. Generalist physicians and NPs/PAs provided 50.8% of all visits. Urban beneficiaries saw more behavioral health specialists (34.3%) than rural beneficiaries (16.1%). NPs and PAs provided more than twice as much of the care for rural beneficiaries (14.8%) as for urban beneficiaries (6.4%). Rural beneficiaries travelled about twice as far as urban beneficiaries. Conclusions: Rural and urban Medicare beneficiaries received care for mood/anxiety disorders from different mixes of health care providers, and ensuring access for rural populations will require innovative solutions.